Spanners, Weak Spanners, and Power Spanners for Wireless Networks - Schindelhauer, Christian; Volbert, Klaus; Ziegler, Martin (Proc. of 15th Annual International Symposium on Algorithms and Computation (ISAAC'04))
For $c in REAL$, a $c$-spanner is a subgraph of a complete Euclidean graph satisfying that between any two vertices there exists a path of weighted length at most $c$ times their geometric distance. Based on this property to approximate a complete weighted graph, sparse spanners have found many applications, e.g., in FPTAS, geometric searching, and radio networks. For geometric searching, it turned out to suffice whether the radius rather than the length of some path between any two vertices is bounded relatively to their geometric distance; this is the defining property of weak spanners. Finally regarding radio network applications, a power spanner accounts for the total energy afforded for a wireless transmission with the requirement that the sum of the squares of the lengths of some path between any two planar vertices must be bounded relatively to the square of their geometric distance (or higher powers up to 6 or even 8). While it is known that any $c$-spanner is also both a weak $C_1$-spanner and a $C_2$-power spanner (for appropriate $C_1,C_2$ depending only on $c$ but not on the graph under consideration), we show that the converse fails: There exists a family of $c_1$-power spanners that are no weak $C$-spanners and also a family of weak $c_2$-spanners that are no $C$-spanners for any fixed $C$ (and thus no uniform spanners, either). However the deepest result of the present work reveals that, surprisingly, any weak spanner is also a uniform power spanner. We further generalize the latter notion by considering $(c,delta)$-power spanners where the sum of the $delta$-th powers of the lengths has to be bounded; so $(cdot,2)$-power spanners coincide with the usual power spanners and $(cdot,1)$-power spanners are classical spanners. Interestingly, these $(cdot,delta)$-power spanners form a strict hierarchy where the above results still hold for any $deltageq2$; some even hold for $delta>1$ while counterexamples reveal others to fail for $delta<2$. In fact we show that in general every self-similar curve of fractal dimension $d>delta$ is no $(C,delta)$-power spanner for any fixed $C$.

Guidance of Users in Interactive 3D-Visualisations of Material Flow Simulations - Mueck, Bengt; Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias; Kortenjan, Michael (Simulation and Visualisation 2004)
The visualisation of manufacturing-processes assists the user in understanding and analysis. Typically he can move free and unguided in a virtual environment which visualizes the entire process. Thus knowledge and conclusions are to some extend acquired on a random base. This article describes the development of a tool, which enables the user to interactively improve significant production processes in the simulation. He moves in a virtual 3D-environment (walkthrough system) and is able to acquire automatically calculated indications for significant processes. At the same time the simulation considers significant objects in a more detailed way. If the viewer is interested in a significant process, he is automatically guided to the relevant location where he can examine the critical situation by modification of the simulation model.

Transcoding von Webinhalten - Oesterdiekhoff, Brigitte (Informatik Spektrum)

Internet Premium Services for Flexible Format Distributed Devices - Oesterdiekhoff, Brigitte (Proceedings of IFIP Working Conference on Distributed and Parallel Embedded Systems (DIPES'04))

Bereichsübergreifendes Toleranzmanagement. Damit es rund läuft - Kretschmer, Ralf; Denzer, Vera; Zimmer, Detmar (QZ - Qualität und Zuverlässigkeit)

Faserverbundwerkstoffe - experimentelle Bestimmung mechanischer Kenngrößen - Koke, Isabel; Funke, Herbert; Ferber, Ferdinand (Posterbeitrag AG Composite)

Integrated Vehicle Dynamics Control Using Active Brake, Steering, and Suspension Systems - Trächtler, Ansgar (Int. J. Vehicle Design)

Verteilte Fahrdynamikregelung mit zeitgesteuerter Architektur am Beispiel des Bosch-Konzeptes VDM - Albert, Amos; Trächtler, Ansgar (13. Aachener Kolloquium Fahrzeug- und Motorentechnik)

Zusammenspiel von regelbaren Feder-/Dämpfersystemen mit ESP - Trächtler, Ansgar (CTI-Konferenz "Federung und Dämpfung")

Integrierte Fahrdynamikregelung mit ESP, aktiver Lenkung und aktivem Fahrwerk - Trächtler, Ansgar (2. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG)

Vehicle Dynamics Management - Benefits of Integrated Control of Active Brake, Active Steering and Active Suspension Systems - Verhagen, Armin; Futterer, Sylvia; Rupprecht, Josef; Trächtler, Ansgar (Proc. FISITA)

Mapping High Quality Textures on an Interactive Globe - Goetz, F.; Boenning, B.; Domik, Gitta (Proc. of The 4th IASTED International Conference on Visualization, Imgaging, and Image Processing)

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Systematic mistuning of bladed disk assemblies with friction contacts - Götting, Florian; Sextro, Walter; Panning, Lars; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
In turbomachinery, friction contacts are widely used to reduce dynamic stresses in turbine blades in order to avoid expensive damages. As a result of energy dissipation in the friction contacts the blade vibration amplitudes are reduced. In case of so-called friction dampers, which are pressed on the platforms of the blades by centrifugal forces, the damping effect can be optimized by varying the damper mass. This optimization can be done by means of a simulation model applying the so-called component mode synthesis and the Harmonic Balance Method to reduce computation time. It is based on the modal description of each substructure. In a real turbine or compressor blading great differences in the magnitude of the individual blade amplitudes occur caused by unavoidable mistuning of all system parameters like contact parameters and natural frequencies of the blades. It may happen that most of the blades experience only small stresses whereas a few blades experience critical stresses. Therefore, it is necessary to consider mistuning for all system parameters to simulate the forced response of bladed disk assemblies with friction contacts. For a mistuned bladed disk the complete system has to be modeled to calculate the dynamic response. In practice, usually the standard deviations instead of the distributions of the system parameters are known. Therefore, Monte-Carlo simulations are necessary to calculate the forced response of the blades for given mean values and standard deviations of the system parameters. To reduce the computational time, an approximate method has been developed and extended for small and moderate standard deviations of the system parameters to calculate the distribution and the envelopes of the frequency response functions for statistically varying system parameters, in the following called statistical mistuning. The approximate method is based on a sensitivity analysis and the assumption of a Weibull distribution of the vibration amplitudes of the blades. Both, the approximate method and the assumption of a Weibull distribution of the vibration amplitudes are validated by Monte-Carlo simulations. By these investigations the influence of different arrangements of the system parameters for given mean values and standard deviations of the vibration amplitudes of the blades can be determined, too. For the present investigations only a small influence of the arrangement of blades with respect to their natural frequencies has been observed. On the other hand, an intentional mistuning of the damper masses and the natural frequencies of the blades in a systematic way, in the following called systematic mistuning, can be investigated to reduce the amplitudes of the system. The simulation results of a systematic mistuning has been validated by a test rig with a rotating bladed disk assembly with friction dampers. The investigations show a good agreement between the simulations and the measurements but only a slight decrease of the maximum amplitudes in case of a systematic mistuning. Copyright {©} 2004 by ASME
Keywords: Friction; Disks

Linear piezoelectric motors and their application - Hemsel, Tobias (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

A novel approach for high power ultrasonic linear motors - Hemsel, Tobias; Mracek, Maik; Wallaschek, Jörg; Vasiljev, Piotr (Ultrasonics Symposium, 2004 IEEE)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable e.g. to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: the electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well organized and controlled to get an optimized drive that is not oversized and costly.
Keywords: drives; electromechanical effects; linear motors; ultrasonic motors; car sunroof; car window; electromechanical behavior; high power ultrasonic linear motors; multiple miniaturized motors; positioning tasks; translatory drive; Costs; Electromagnetic forces; Frequency; Laboratories; Manufacturing; Mechatronics; Micromotors; Ultrasonic imaging; Vibrations; Voltage

Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Design criteria for piezoelectric transformers - Littmann, Walter; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics)

Self configuration of miniature ultrasonic linear motors - Mracek, Maik; Wallaschek, Jörg; Hemsel, Tobias (Proceedings of the 18th International Congress on Acoustics)

Asymmetrical Underplatform Dampers in Gas Turbine Bladings: Theory and Application - Panning, Lars; Popp, Karl; Sextro, Walter; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
During operation, the rotating blades of a gas turbine are subjected to centrifugal forces as well as fluctuating gas forces, resulting in blade vibrations. In addition to material damping, aerodynamical and blade root damping, underplatform dampers are widely used to increase the amount of damping and to decrease blade vibration amplitudes. The friction forces generated by the relative displacements between the underplatform damper and the blade platforms provide a significant amount of energy dissipation. In practice, a number of different underplatform damper designs are applied. Basically, these are wedge dampers with flat contact areas, cylindrical dampers with curved surfaces or asymmetrical dampers with both flat contact surfaces on one side and curved contact surfaces on the other. The latter damper type combines the advantages of both the wedge and the cylindrical damper by preventing the damper from pure rolling on the one hand as it has been observed for cylindrical dampers and on the other hand, avoiding a diverged plane area contact in case of a wedge damper, causing a damper lift-off. This paper will focus on the investigation of cylindrical and asymmetrical underplatform dampers. A comparison between measurements of rotating assemblies in Siemens PG gas turbines (V84.2, V64.3A and V94.3A(2)) under test and real operating conditions with cylindrical and asymmetrical underplatform dampers and the predictions of the developed theoretical model are presented. Special attention is paid to the frequency shift due to the application of an underplatform damper, since in particular for stationary gas turbines, in addition to the amplitude reduction, the accurate prediction of the resonance frequency is of major interest. Copyright {©} 2004 by ASME
Keywords: Dampers; Gas turbines